ANALISIS KUALITAS PELAYANAN PENGURUSAN DOKUMEN AKTA KELAHIRAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN JEPARA - Yundito Rizqi Setyawan; Dyah Lituhayu; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
A birth certificate is legal proof of a person's birth issued by Disdukcapil. This evidence is one of the documents which must be owned because it is used as a basis for obtaining public services and preventing the risk of crime. However, the facts show that there are still many people who do not have birth certificates, especially in Jepara Regency. This condition was exacerbated by the realization which Disdukcapil's performance did not meet the targets set. This study aims to determine the quality of service and what factors impede the quality of service for processing birth certificate documents at the Jepara Regency Population and Civil Registration Office. The method used is a descriptive qualitative method of conducting interviews, observation, and documentation. The results show which from the tangibles dimension Disdukcapil provides various infrastructure facilities, as well as media which can be used by applicants, as well as rules related to the ethics of dressing officers, reliability shows that Disdukcapil pays attention to the reliability of officers as the prime mover of the facility by conducting short training to increase the ability to operate the facility and the ability communication which is strengthened by basic guidelines in service delivery/SOP, responsiveness shows the responsiveness of officers in providing services and officers who are indifferent/does not respond to complaints online, assurance shows the unclear length of time it takes the service applicant to complete the entire service process, free service, safe personal data, and easy access to services, and empathy shows Disdukcapil fairness even without a queue number, services are carried out in the order of arrival/request. Then there are inhibiting factors such as the high workload received, the lack of awareness/responsiveness of officers in answering online complaints and the lack of public awareness to immediately take care of them, and the emergence of brokers due to the ease of the management system.